"Holding the City's Feet to the Fire": Lessons Learned From Oakland's Implementation of Measure HH Sugar-Sweetened Beverage Tax. Issue 1 (14th January 2022) - Asada, Yuka; Chriqui, Jamie F.; Pipito, Andrea A.; Taher, Sabira; Powell, Lisa M.
Abstract : Context: Sugar-sweetened beverage (SSB) taxes offer a promising public health strategy to decrease consumption of sugary beverages. To date, 7 US cities have successfully implemented SSB taxes; however, only a few studies have examined adoption and implementation processes. Objectives: To describe public health and policy lessons learned during the first 2.5 years of implementation of the Oakland, California, penny-per-ounce SSB tax, Measure HH. Design: A mixed-methods, longitudinal, qualitative case study was conducted using a combination of key informant interviews with implementation stakeholders as well as analyses of archival documents and media documents from 2016 to 2019. Interviews were digitally recorded and professionally transcribed. Interview transcripts, archival documents, and media documents were analyzed by 3 coders using Atlas.ti v8. Analyses employed principles of constant comparative analysis to identify themes related to lessons learned. Setting: Oakland, California. Participants: Key informants (n = 15), archival documents (n = 43), and media documents (n = 90). Intervention: Oakland, California's SSB tax (Measure HH). Results: Implementation lessons included both success stories and challenges. Successes included contracting a third-party tax administrator to support tax collection and education; leveraging a pro-tax coalition to counteract industry attacks and to protect tax revenue; and offering "quick win" funding to support local needs. Challenges were associated with implementing a "general" tax versus a "special" tax; the lack of explicit revenue allocation in the ordinance to support city-level implementation and oversight; and, the original ordinance language for tax application to distributors. Conclusions: The study offers a range of recommendations—derived from lessons learned over several years of implementation—to policy makers and advocates engaged in SSB tax adoption and implementation efforts in their jurisdictions. SSB tax implementation requires sufficient agency administrative capacity and a strong pro-tax coalition that engages local community organizations to respond to public health needs.